Optimization Using D-Optimal Design of Nanostructured Lipid Carrier (NLC) with Variation of Surfactants and Co-surfactant - Wafa'ul Athiyyah; Widji Soeratri; Noorma Rosita; Siti Hartini Hamdan (Universitas Airlangga, 2025)
Background: Nanostructured lipid carriers (NLC) are topical delivery systems designed to address the challenges associated with active ingredients, such as poor solubility and limited skin penetration. NLCs incorporate surfactants, such as sorbitan monooleate and lauryl glucoside, to stabilize the system, while the addition of soy lecithin as a co-surfactant further enhances NLC stability. A D-optimal design was employed to optimize the NLC components, ensuring that the formulation achieved the desired characteristics. Objective: To determine the optimal NLC formulation. Method: Optimization was conducted using the D-optimal design method. The NLCs were prepared using the high-shear homogenization method with an Ultra-Turrax device. Characterization included measuring the particle size, polydispersity index (PDI), pH, and creaming index. Results: All formulations resulted in homogeneous emulsions with a white color, slight aroma of castor oil, smooth texture, and thick consistency. The particle sizes ranged from 200 to 500 nm, although the polydispersity index was not significantly influenced by surfactants or co-surfactants. All the formulations maintained an appropriate pH range for skin compatibility and product stability. The %creaming index demonstrated that the co-surfactant effectively reduced creaming in the NLCs. Conclusion: The optimal formulation consisted of 0.284% sorbitan monooleate, 3.429% lauryl glucoside, and 0.287% soy lecithin.